Workshops of the eighth international brain–computer interface meeting: BCIs: the next frontier. Issue 2 (3rd April 2022) - Huggins, Jane E.; Krusienski, Dean; Vansteensel, Mariska J.; Valeriani, Davide; Thelen, Antonia; Stavisky, Sergey; Norton, James J.S.; Nijholt, Anton; Müller-Putz, Gernot; Kosmyna, Nataliya; Korczowski, Louis; Kapeller, Christoph; et al.
ABSTRACT: The Eighth International Brain–Computer Interface (BCI) Meeting was held June 7–9, 2021 in a virtual format. The conference continued the BCI Meeting series' interactive nature with 21 workshops covering the breadth of topics in BCI (also called brain–machine interface) research. Some workshops provided detailed examinations of methods, hardware, or processes. Others focused on BCI applications or user groups. Several workshops continued consensus building efforts designed to create BCI standards and improve comparisons between studies and the potential for meta-analysis and large multi-site clinical trials. Ethical and translational considerations were the primary topic for some workshops or an important secondary consideration for others. The range of BCI applications continues to expand, with more workshops focusing on approaches that can extend beyond the needs of those with physical impairments. This paper summarizes each workshop, provides background information and references for further study, summarizes discussions, and describes the resulting conclusion, challenges, or initiatives.